Impact of arm circumference on clinical outcomes in patients undergoing transcatheter aortic valve replacement. (June 2022) - Shibata, Kenichi; Yamamoto, Masanori; Kameshima, Masataka; Fujiyama, Hiroaki; Sano, Taisei; Kagase, Ai; Tokuda, Takahiro; Adachi, Yuya; Yamaguchi, Ryo; Shimura, Tetsuro; Iritani, Naoki; Murase, Kazuma; et al.
Abstract: Background: Although Arm circumference (AC) is considered to be a predictor of clinical outcomes of transcatheter aortic valve replacement (TAVR), limited data are available on the impact of this anthropometric measurement. This study aimed to investigate the clinical impact of AC on the outcomes of patients who underwent TAVR. Methods: AC was investigated in consecutive patients who underwent TAVR between March 2014 and May 2018. Patients were divided into low AC (n = 220) and high AC (n = 127) groups by a classification and regression tree (CART) survival model, and their baseline characteristics and mortality were compared. The correlations of AC with other frailty markers were also evaluated. Results: One-year clinical follow-up was completed in 100% of cases, and 89 patients (31 men, 58 women) died during the median follow-up period of 825 days. The low AC group was more fragile than the high AC group, and the AC value was significantly correlated with each frailty marker (all p < 0.05). The Cox regression analysis demonstrated the independent association of mortality with low AC (HR: 2.56, 95% confidence interval [CI]: 1.47–4.46, p < 0.001). When AC was compared to conventional prediction models of survival, the net reclassification improvement and the integrated discrimination improvement analysis showed significant improvements in predicting outcomes after including the AC with other frailty markers (all p < 0.05). Conclusions: The AC is related to frailty markers and is an important surrogate marker for predicting worse clinical outcomes after TAVR. Assessment of AC may be considered when deciding on TAVR.